Globalization and Growth in the Twentieth Century - Crafts, N. (IMF Working Papers; Working Paper, 2000)
This paper reviews the experience of economic growth during the twentieth century with a view to highlighting implications for both growth economists and policy-makers. The unprecedented divergence in income levels between the OECD economies and many developing countries is documented but so too is a more optimistic picture of widespread progress in terms of the Human Development Index. Various aspects of the changes in economic structure are explored in terms of their implications for growth performance both in retrospect and prospect. The possibility that the growth process will lead to another globalization backlash reminiscent of the 1930s is analyzed.